THE THEME OF THE HOMELAND IN THE WORKS OF I. A. ILYIN (World Bulletin of Education and Learning, 2025)
The article is devoted to the analysis of one of the central categories of the philosophical heritage of I. A. Ilyin — the concept of Homeland. The peculiarities of its interpretation in the philosopher’s works are considered, with special attention given to the spiritual nature of Homeland, its distinction from material and state definitions, and its role in shaping national identity and patriotism. Ilyin’s critique of the Marxist approach to Homeland is highlighted, and his own understanding of it as the spiritual unity of a people, embodying their system of values, moral order, and creative achievements, is revealed. It is emphasized that the concept of Homeland in Ilyin’s philosophy has both ontological and axiological dimensions, allowing it to be viewed as a universal category significant for both the individual and society as a whole.
Keywords: I. A. Ilyin; Homeland; spiritual reality; sacred value; patriotism.